2022
DOI: 10.3390/jpm12040588
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Guided Zygomatic Implant Placement after Maxillectomy

Abstract: Zygomatic implants are used in patients with maxillary defects to improve the retention and stability of obturator prostheses, thereby securing good oral function. Prosthetic-driven placement of zygomatic implants is even difficult for experienced surgeons, and with a free-hand approach, deviation from the preplanned implant positions is inevitable, thereby impeding immediate implant-retained obturation. A novel, digitalized workflow of surgical planning was used in 10 patients. Maxillectomy was performed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…After removing duplicates ( n = 56), 51 articles were screened using title-abstract-keyword reading, leaving 35 reports eligible (substantial agreement, κ = 0.95). After full-text reading and a subsequent search for relevant citations, 14 studies were included in this systematic review [ 8 , 10 , 11 , 12 , 13 , 14 , 15 , 19 , 32 , 33 , 34 , 35 , 36 , 37 ] (100% of agreement among the reviewers) ( Figure 1 ). One current retrospective study from Wu included [ 19 ], and other fives studies from the same team (Shanghai Jiaotong University) were excluded due to the same population were collected in Wu’s publication [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After removing duplicates ( n = 56), 51 articles were screened using title-abstract-keyword reading, leaving 35 reports eligible (substantial agreement, κ = 0.95). After full-text reading and a subsequent search for relevant citations, 14 studies were included in this systematic review [ 8 , 10 , 11 , 12 , 13 , 14 , 15 , 19 , 32 , 33 , 34 , 35 , 36 , 37 ] (100% of agreement among the reviewers) ( Figure 1 ). One current retrospective study from Wu included [ 19 ], and other fives studies from the same team (Shanghai Jiaotong University) were excluded due to the same population were collected in Wu’s publication [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 2016, a modified surgical guide with double sleeves, designed to stabilize the long drill and to overcome the deviation, was introduced [ 9 ]. Later, studies focused on utilizing this modified guide concept to assist in ZI placement with increased intra-operative safety and accuracy [ 10 , 11 , 12 , 13 , 14 , 15 ]. Gecchi et al demonstrated that the accuracy of ZI placement with a modified surgical guide was superior to the free-hand approach, particularly at the level of the zygomatic bone [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, an accurate cutting of the tumor is realized under the guidance of the 3D printed cutting guide plate [124]. Vosselman et al [125] performed a maxillectomy using the 3D printed surgical guide plate, achieving a precise placement of the zygomatic implant (figures 6(a)-(c)). The degree of accuracy of the placement is high (average deviation is 1.73 ± 0.57 mm and 3D angle deviation is 2.97 ± 1.38 • ).…”
Section: Cuttingmentioning
confidence: 99%
“…We have never used or wished to use computerized guides to place zygomatic implants in these patients for a variety of reasons. We do however recognize the difficulty of placing these implants for new users who may well benefit from employing this technology if available and are aware of units who adopt this approach 3 . In addition, there is a two‐day hands‐on training course specifically focused on the techniques required.…”
mentioning
confidence: 99%